Wykorzystanie crowdsourcingu w celu dywersyfikacji źródeł innowacji - Malinowski, Bartosz (Funkcjonowanie e-biznesu. Zasoby, procesy, technologie, 2015)
The aim of the article is to analyse a relationship between crowdsourcing and Open Innovation using the example of practical implentation in form of My Starbucks Idea internet platform. It is a website and a platform with Starbucks’ customers in mind, who can use it in order to submit their own ideas. In accordance to the platform’s value proposition which is „your ideas, your Starbucks” the customers work together on improving their beloved brand – its products, service, interior design etc. The gathered information and conclusions might help in understanding the benefits of the synergy of crowdsourcing and Open Innovation – marketing-wise, to company and the customers alike.